Amplifying Youth Voices Using Digital Technology: A Case Study in Collaborative Research With Youth Service Organizations - Rachel M. Magee; Amy M. Leman; Gowri Balasubramaniam (Journal of Participatory Research Methods)
This paper presents three participatory methods informed by design techniques for engaging youth and youth services providers in research activities online. We detail two data collection methods: 1) a priming activity completed before a focus group to prompt reflection before direct interaction with the research team; and 2) a focus group activity imagining future organizational goals. We also share our technique for collaboratively analyzing preliminary research findings with a focus group activity. We developed these methods as a part of a larger research project examining how teens and those who provide services to teens through community programs conceptualized success in their experiences, sense of community, and program implementation. This paper discusses work with five organizations in a mid-size community in the midwestern United States during the COVID-19 pandemic (July 2021–February 2022). We aimed to amplify the voices and perspectives of teens in both research and the organizations they engaged in, bringing their participation to our data collection and analysis and to the adults and decision-makers of community organizations. We wanted to understand how youth or teens, defined as 13–19 years old, describe successful experiences in these out-of-school settings, how adults define success, and to identify connections and differences between these two perspectives. This paper details the techniques we developed and tested, shares examples from our research, and discusses the impacts and implications of these methods for future participatory work. We contribute evidence for the value of drawing on design methods for participatory methods, articulate benefits and considerations for intentionally doing so online, and share techniques that emphasize voice in both research and organizational partners’ program development and management.